A Purpose Conventional Use of oxytocic during the Puerperium - Carbonel Holguin, Juan M. (1965)
The purpose of this thesis is to try to demonstrate , through a comparative study , whether it is justifiable or not, the routine use of oxytocic during the immediate postpartum period ; analyzing the study from four perspectives : loss of lochia , uterine involution , and consistency of the uterus postpartum abdominal pain. Since 1807 when John Stearns of Sara toga, New York, a crude extract isolated erqotina begins to gain momentum citócicas the use of substances in the obstetric field; later , in 1934 , to isolate and standardize the alkaloid ergonovine , Davis et al. , helped to further the use of oxytocic pospartum were routinely used in ( 6). The reasons given for the use of these drugs by mouth are: a) no side effects , b ) cause a rapid involution of uterus , c ) decrease the puerperal blood loss and reduce morbidity postpartum d ) may condition the expulsion of retained placental remnants . However, these arguments do not require clinical thinking about the absolute necessity of the use of drugs for the above effects ( 1). Friedman ( 13) using a series of oxytocic during the immediate postpartum period , concludes that the vast majority of patients r = want of such drugs for puerperal uterine -contraction . Notes that the oxytocic have practical application in cases of overdistended uteri ( twin pregnancy , hydramnios , etc. . ) And limp , but not in cases of conventionally normal utero.